PEMAHAMAN KONSEP MATEMATIS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN INQUIRI TERBIMBING - Gunur, Bedilius; Lalus, Eleonora; Ali, Ferdinandus Ardian (Edumatica : Jurnal Pendidikan Matematika, 2019)
Abstract The ability to understand concepts is very important and becomes the basis for supporting the solving of mathematical problems. The connection between one concept and another concept and one topic with another topic is a characteristic of learning mathematics. The relationship requires that each student must have the ability to understand the concepts well, but it cannot be denied that the ability to understand mathematical concepts is still low, as happened to theLangke Rembong 4Junior High School students. Learning innovation needs to be done to achieve a good understanding of concepts. This study aims to compare the understanding ability of mathematical concepts of students who follow a guided inquiry learning model with students who take direct learning. The research design uses Posttest only control group design. The population is all eighth grade students of Langke Rembong 4 Junior High School, totalling230 students. Sampling is done by random sampling with equality test between classes.It is then obtained class VIII A as the experimental class and class VIII C as the control class. Data collection uses tests in the form of description questions. Data analysis uses t-test with normality test and homogeneity test for the assumptions. The results show that the students who follow the guided inquiry learning have higher understanding of mathematical concepts than those who are taught with direct learning model. Keywords: inquiry, understanding of mathematical concepts